The natural diet of the mud crab (Scylla serrata) in Lawele Bay, Southeast Sulawesi, Indonesia - Sara, La; Aguilar, Riza O.; Laureta, Liberato V.; Baldevarona, Rodolfo B.; Ingles, Jose A. (2007)
The gastric mill content of 139 specimens of Scylla serrata in varying sizes was examined using percentage composition and percentage occurrence to evaluate its natural diet and food composition at different growth stages and seasons. The gastric mill content index (GMI) was analyzed to determine seasonality of food composition. The relationship between gastric mill volume (GMV) and carapace width (CW) of S. serrata portrayed a linear regression when both variables were expressed in terms of logarithm. GMV increased linearly with increasing CW.

S. serrata is a bottom feeding organism, eating a wide variety of sessile and slow-moving benthic organisms as well as plant fragments. The natural diet of S. serrata at all growth stages primarily consisted of unidentified organic matter including the meat of various organisms. The second most common component of the natural diet was Sargassum/eelgrass. Fish, molluscs and crustaceans were frequently found in the gastric mill content of S. serrata at all growth stages. Gastropods were not preferred as shown in their low percentage composition and occurrence. Inorganic materials were found in the gastric mill, probably ingested during feeding. The diet composition suggests that S. serrata is omnivorous and that its feeding behavior is that of a scavenger. Although these food items were not significantly different among stages and seasons (p>0.05), they were high during the north monsoon and decreased during the south monsoon period. It could be related to the high water productivity of Lawele Bay during the north monsoon, which may suggest that the growth of S. serrata is high because molting takes place frequently during this period.
Keywords: Crabs -- Feeding and feeds